Does the effect of power distance moderate the relation between person environment fit and job satisfaction leading to job performance? Evidence from Afghanistan and Pakistan - Habib Gul; Muhammad Usman; Yuxin Liu; Zahid Rehman; Khalil Jebran (Future Business Journal, 2018)
This study examines the relation between person-environment (P-E) fit with job satisfaction and job (task) performance. This cross-national study is based on faculty members of universities from Kabul (180) and Islamabad (270). Data is collected through self administered questionnaires and is tested following the Baron and Kenny (1986) moderation and mediation procedures. The studycontend that power distance moderates the relationship between P-E fit and job satisfaction. Contrary to expectation, power distance does not moderate the hypothesized relationship. This study finds that individual's satisfaction from high power distance culture depends on their cultural norms because they give more preference to cultural norms than their own needs and demands. Moreover, results show the direct relationship of P-E fit with job performance in Afghanistan (Kabul) and Pakistan (Islamabad). We compared the results of hypothesized model cross-nationally and find some variation regarding employee's job satisfaction. Job satisfaction partially mediates the relationships between P-E fit and job performance in Kabul, while in Islamabad job satisfaction fully mediate the relationship between P-E fit and job performance. By asserting the role of culture, this study developed practical implications for both theorists and practitioners.
Keywords: 650; Afghanistan; Job performance; Job satisfaction; P-E Fit; Pakistan; Power distance